2009
DOI: 10.1063/1.3117965
|View full text |Cite
|
Sign up to set email alerts
|

Structure of nitrous oxide-carbon dioxide alloys

Abstract: Structure of N 2 O-CO 2 solid mixtures was investigated by transmission electron diffraction over the entire range of their mutual concentrations. In the temperature range 5-65 K the experimental data indicate no phase separation in these alloys. The average structure of the solutions belongs to the Pa3 symmetry. The behavior of the concentration dependence of the lattice parameter has a nonmonotonic character, displaying a sharp step, the positions of which on the concentration scale depends on the deposition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…This augments a study by Solodovnik in which he observed these CO 2 –N 2 O systems as powders at very low temperatures (5–65 K) via transmission high energy electron diffraction measurements. 32 …”
mentioning
confidence: 99%
“…This augments a study by Solodovnik in which he observed these CO 2 –N 2 O systems as powders at very low temperatures (5–65 K) via transmission high energy electron diffraction measurements. 32 …”
mentioning
confidence: 99%